2012
DOI: 10.2147/ijn.s34588
|View full text |Cite
|
Sign up to set email alerts
|

Plausible antioxidant biomechanics and anticonvulsant pharmacological activity of brain-targeted β-carotene nanoparticles

Abstract: β-Carotene has been established as a known free radical scavenger with chainbreaking antioxidant properties. It has been documented for the treatment of epileptic convulsions at a 200 mg/kg body weight dose. The reported pathogenesis for epileptic convulsions is oxidative stress. Hence, experimental epileptic convulsions via oxidative stress was induced in albino mice epileptic models (maximal electroshock seizure and pentylenetetrazole [PTZ]). A dose concentration equivalent to 2 mg/kg was efficaciously admin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…Results show that a higher amount of antisolvent resulted in higher PDI, varying from 0.29 to 0.20, at 0.7 mL/min flow rate and 0.4% zein concentration. PDI measures the homogeneity of the NPs dispersion, PDI values greater than 0.5 can represent aggregation of particles [ 41 ] but for the tested conditions all measurements stayed below this value.…”
Section: Resultsmentioning
confidence: 99%
“…Results show that a higher amount of antisolvent resulted in higher PDI, varying from 0.29 to 0.20, at 0.7 mL/min flow rate and 0.4% zein concentration. PDI measures the homogeneity of the NPs dispersion, PDI values greater than 0.5 can represent aggregation of particles [ 41 ] but for the tested conditions all measurements stayed below this value.…”
Section: Resultsmentioning
confidence: 99%
“…β-Carotene is an antioxidant known for its epileptic convulsions. Bioavailability and stability of polysorbate-80-coated β-carotene nanoparticles for epileptic convulsions in mice models was found to be higher when compared to unmodified β-carotene (49). …”
Section: Targets For Mitochondrial Dysfunction Related Diseasesmentioning
confidence: 96%
“…DQA was also used with TPGS1000, known as vitamin E polyethylene glycol succinate, to construct mitochondria targeting liposomes for the delivery of chemotherapeutic drug, topotecan hydrochloride a topoisomerase I inhibitor. These mitochondria targeted topotecan entrapped liposomes demonstrated higher efficacy for treatment of chemo-resistant cancer and showed inhibition of metastases in vivo (49). …”
Section: Mitochondrial Targets For Cancermentioning
confidence: 99%
“…Solid lipid nanoparticles loaded with carbamazepine (Samia et al, 2012) and PLGA nanoparticles loaded with β-carotene (Yusuf et al, 2012) have been found to show more potential for anticonvulsant effect than nanoemulged loaded carbamazepine and polysorbate-80 coated PLGA nanoparticles, respectively. In a rat model, liposomal muscimol formulation (Kohane et al, 2002) has been reported to suppress focal seizures while producing minimal histological alterations, and amiloride loaded liposomes (Ali et al, 2007) demonstrated higher anticonvulsant potential in comparison to the free drug in a mice model.…”
Section: Epilepsymentioning
confidence: 99%